Identifikasi Ekspresi Manusia Berdasarkan Binar Mata Menggunakan Metode Transformasi Hough - Ahmad Nur Taufiqurrahman (Lembaga Pengembangan Kinerja Dosen, 2025)
Kabupaten Sukabumi has 47 districts with a total area of 416,415.179 hectares. The population of Kabupaten Sukabumi (2025) reaches 2,660,138 people. This high growth rate and high population density need to be balanced by a high rate of hospital growth to ensure adequate health services, which will certainly increase as the population grows. This study seeks to determine the best location for the construction of the next hospital. The method used is multi-criteria analysis with the multi-ring buffer method. The dataset was processed using the open source GIS application QGIS 3.4. Bratislava. The research began with the formulation of spatial criteria used in this study, namely: 1) twelve subdistricts in Kabupaten Sukabumi that became the area of interest (AOI) of the study, 2) having a relatively high population density/growth rate/number, 3) the selected areas must be outside the service areas of the four existing hospitals, and 4) located on main roads with a setback of 300 meters. The results showed that three priority locations met the criteria. Priority 1 was the Gunungguruh Area with an area of approximately 494.576 hectares located around Dayeuhluhur, Lembursitu, and Kertaraharja, or located on part of the Pelabuhan II main road. Priority 2 is the Cicantayan Area with an area of approximately 349.80 hectares located around Desa Cicantayan, Sunggapan, and Nanggerang, or located on part of Mama Oyon and Cicantayan-Bojong highways. Priority 3 is in the Cikembar Area, which stretches west-east from Cibungur to Pasar Pangleseran, and north-south from Bojong-Cibuni to Desa Padabeunghar. These three areas can be considered by policymakers before establishing a hospital in Kabupaten Sukabumi.